Exploring the pedagogical strategies used by Namibian secondary school History educators in teaching reading comprehension - Kambindji, Absalom Ndamutala (Rhodes University, 2026)
Language is central to learning as it is a conduit for conceptualisation, critical thinking, discourse and cognitive engagement. This suggests that despite the content focus, all learners in Grade 4 to 12 assimilate knowledge by listening, speaking, reading and writing about the new concepts. Consequently, the importance of language in learning has led to a continuous inquiry into instructional practices that simultaneously enhance language development and content learning. In Namibia, where learners use English as a second language as a medium of instruction, Language Across the Curriculum (LAC) has been advanced as a possible solution to developing learners’ language competence. In contexts where English is used as a medium of instruction and the language of learning and teaching (LoLT), LAC is usually referred to as English Across the Curriculum (EAC) and Reading Across the Curriculum (RAC). The initial teachers’ preparation curriculum rarely focuses explicitly on preparing preservice content teachers on how to infuse reading and content learning in Namibia. To address the paucity of studies emanating from the Namibian context, this study explored the pedagogical strategies used by History educators when teaching reading comprehension. Purposive sampling was used to select five experienced Grade 8 History educators for this study. Data was collected using document analysis, classroom observation and two types of semi-structured interviews, namely interviews focused on the participants’ lesson planning process and interviews focused on the participants’ actions and decisions during practice. Inductive thematic analysis was also used as a framework to analyse the data. The study findings indicate that the participants activated learner’s linguistic schema in pre-reading activities using dictionaries to define new words and emphasis on pronunciation of the names of people and places correctly. Importantly, schema theory suggests that content educators often use schema-driven instruction to activate students’ prior knowledge, and reflective practice suggests that teaching experience with thoughtful reflections can foster awareness, development, and personal growth. The findings from this study could be beneficial for policymakers, other researchers in the field, Grade 8 History educators and other content subject educators.
Keywords: Interdisciplinary approach in education (http://id.loc.gov/authorities/subjects/sh85067231); History teachers (http://id.loc.gov/authorities/subjects/sh85061256); Content area reading (http://id.loc.gov/authorities/subjects/sh85031538); Reading comprehension (http://id.loc.gov/authorities/subjects/sh85111686); Namibia (http://id.loc.gov/authorities/names/n79039884-781); Content creator (https://www.wikidata.org/wiki/Q109459317)